Emerging trends in biopolymer edible coatings for enhancing the shelf life of neglected and underutilized crops - Mathura, Sarah R.; Maharaj, Rohanie; Ratkovich, Nicolas (Frontiers in Food Science and Technology, 2025)
Neglected and underutilized species (NUS) are nutrient-dense crops, offering high concentrations of essential nutrients relative to their calorie content. These crops are increasingly explored for their potential to meet global consumption demands while promoting ecosystem biodiversity sustainably. However, their commercialization has been limited by short shelf life and significant postharvest losses. One promising solution is the use of biopolymer edible coatings as an alternative to plastic packaging, which could extend the shelf life of these crops. This review examines research conducted over the past decade on preserving underutilized crops with biopolymer coatings and suggests potential directions for future studies. It covers the sources of biopolymer coatings, their benefits and drawbacks, application methods, and strategies to overcome challenges associated with different biopolymers. While various coating formulations have shown promising results, the commercialization of these coatings for underutilized crops remains limited. The review also identifies key research gaps that must be addressed to bridge this gap.